SPE Annual Technical Conference and Exhibition 1995
DOI: 10.2118/30595-ms
|View full text |Cite
|
Sign up to set email alerts
|

Shear Sonic Interpretation in Gas-Bearing Sands

Abstract: fax 01-214-952-9435. ' AbstractThe introduction, a few years ago, of shear dipole sonic logs gave the industry the possibility to record high-quality shear and compressional slownesses in soft formations. Data sets were acquired and analyzed on Vp/Vs versus i1tc crossplots. Trends were identified in sands and shales and were matched with semi-empirical correlations based on the Gassmann formalism. These trends can be used to quality control shear logs and for quicklook lithology interpretation. The presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
179
1
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(196 citation statements)
references
References 19 publications
9
179
1
4
Order By: Relevance
“…For water saturation less than 99.9%, the harmonic average gives underestimated results. For this reason, Brie et al (1995) formulate the effective K f as…”
Section: Porous Media Homogenizationmentioning
confidence: 99%
See 1 more Smart Citation
“…For water saturation less than 99.9%, the harmonic average gives underestimated results. For this reason, Brie et al (1995) formulate the effective K f as…”
Section: Porous Media Homogenizationmentioning
confidence: 99%
“…4) The pores are saturated with one single (or one effective) fluid phase. Domenico (1976) and Brie et al (1995), for instance, use simple averages, partly empirical, to compute the properties of the effective fluid. However, the patchy saturation theory (White, 1975;Dutta and Odé, 1979) makes it possible to take into account the spatial distribution of each fluid phase, which modifies seismic waveforms (dispersion and attenuation).…”
Section: Introductionmentioning
confidence: 99%
“…The density mix is straightforward using the volume The acoustic properties are mixed using Brie's formula (Brie et al 1995) to account for the variation in distribution of the different fluids within the pore space,…”
Section: Fluid Mixingmentioning
confidence: 99%
“…However, we found that to fit the observed velocity in areas where the gas saturation was non-zero, the gas effect had to be reduced. The overestimation of the gas effect on fluid bulk modulus by the Wood's mixing law, Equation (6), has been observed by Brie et al (1995). A better match between predicted and observed velocity could be achieved by a simple correction to the gas term in Equation (6) (1)- (5), (7), (8), and (10), with constants listed in Table 2, to calculate time-lapse changes in reservoir parameters.…”
Section: A Rock-properties Modelmentioning
confidence: 99%